2015
DOI: 10.1097/qad.0000000000000707
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of durability of first-line antiretroviral therapy regimen and time from first-line failure to second-line antiretroviral therapy initiation

Abstract: Background We described reasons for switching to second-line antiretroviral treatment (ART) and time to switch in HIV-infected children failing first-line ART in West Africa. Methods We included all children aged 15 years or less, starting ART (at least three drugs) in the paediatric IeDEA clinical centres in five West-African countries. We estimated the incidence of switch (at least one a drug class change) within 24 months of ART and associated factors were identified in a multinomial logistic regression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 16 publications
4
22
0
Order By: Relevance
“…Because the tuberculosis data were incompletely reported, we could not completely explore this hypothesis. The finding that older age at initiation of ART is associated with an increased likelihood of switching has been previously reported 11,13 and could be partly due to the lack of available paediatric formulations for young children and poorer adherence among adolescents than among younger children. The increased incidence of switching among male patients has been previously reported in paediatric and adult cohorts, 11,12,29 and warrents further study.…”
Section: Discussionsupporting
confidence: 53%
“…Because the tuberculosis data were incompletely reported, we could not completely explore this hypothesis. The finding that older age at initiation of ART is associated with an increased likelihood of switching has been previously reported 11,13 and could be partly due to the lack of available paediatric formulations for young children and poorer adherence among adolescents than among younger children. The increased incidence of switching among male patients has been previously reported in paediatric and adult cohorts, 11,12,29 and warrents further study.…”
Section: Discussionsupporting
confidence: 53%
“…Twenty-two (62.9%) of the deaths occurred during the first year of follow-up. The total number of deaths that occurred in this study is much lower than was reported in a study conducted in Debre-Markos Hospital, Ethiopia, where 40.7% of patients died [ 18 ]. Moreover, data from Senegal, Malawi, and Tanzania have indicated high rates of HIV-related mortality, ranging from 24.2 to 44.0% [ 30 ], in contrast to the present study.…”
Section: Discussionmentioning
confidence: 57%
“…This rate is lower than the rate of switching that has been reported from Uganda at 24 months (65.0%) following a VF [ 21 ]. A study has also reported an association between poor adherence and switch to second-line regimen [ 26 ]. In addition to the behaviour of patients while receiving a specific regimen, the ability of care providers to take a clinical decision to switch also depends on the availability of second-line and even third-line ARV regimens.…”
Section: Discussionmentioning
confidence: 99%